2017
DOI: 10.4049/jimmunol.1601948
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Myeloid TLR4 Mediates T Lymphocyte Polarization after Traumatic Brain Injury

Abstract: Traumatic brain injury (TBI) is a major public health issue, producing significant patient mortality and poor long-term outcomes. Increasing evidence suggests an important, yet poorly defined, role for the immune system in the development of secondary neurological injury over the days and weeks following a TBI. Herein, we tested the hypothesis that peripheral macrophage infiltration initiates long-lasting adaptive immune responses after TBI. Using a murine controlled cortical impact model, we used adoptive tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
65
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 58 publications
(72 citation statements)
references
References 77 publications
(90 reference statements)
6
65
1
Order By: Relevance
“…Consistent with a role for TLR4 in mediating M1 macrophage polarization [222] and in reprogramming M2 macrophages toward a M1 phenotype [223, 224], we reported that both TLR4 −/− mice and C3H/HeJ mice, which contain a spontaneous inactivating point mutation in the TLR4 signaling domain, exhibited a reduction in M1 polarization over the first 72h after experimental TBI [225]. Of note, a progressive increase in the ratio of M1:M2 macrophages temporally correlated with evolving neurological injury, including white matter loss and reduced brain volume, after TBI [37, 187, 225, 226]. In line with the aforementioned studies, M1 macrophages accumulated within peri-contusional white matter, within grey matter, and within the contralateral cortex by d3 after TBI, preceding oligodendrocyte apoptosis and widespread myelin loss (hallmarks of white matter injury) over the next several weeks [215].…”
Section: Is Microglial Activation the Cellular Link Between Damp Rsupporting
confidence: 70%
See 3 more Smart Citations
“…Consistent with a role for TLR4 in mediating M1 macrophage polarization [222] and in reprogramming M2 macrophages toward a M1 phenotype [223, 224], we reported that both TLR4 −/− mice and C3H/HeJ mice, which contain a spontaneous inactivating point mutation in the TLR4 signaling domain, exhibited a reduction in M1 polarization over the first 72h after experimental TBI [225]. Of note, a progressive increase in the ratio of M1:M2 macrophages temporally correlated with evolving neurological injury, including white matter loss and reduced brain volume, after TBI [37, 187, 225, 226]. In line with the aforementioned studies, M1 macrophages accumulated within peri-contusional white matter, within grey matter, and within the contralateral cortex by d3 after TBI, preceding oligodendrocyte apoptosis and widespread myelin loss (hallmarks of white matter injury) over the next several weeks [215].…”
Section: Is Microglial Activation the Cellular Link Between Damp Rsupporting
confidence: 70%
“…Toward this end, “classically activated” (M1) macrophages exhibit a pro-inflammatory phenotype whereas “alternatively activated” (M2) macrophages release anti-inflammatory mediators to dampen immune responses [220, 221]. Consistent with a role for TLR4 in mediating M1 macrophage polarization [222] and in reprogramming M2 macrophages toward a M1 phenotype [223, 224], we reported that both TLR4 −/− mice and C3H/HeJ mice, which contain a spontaneous inactivating point mutation in the TLR4 signaling domain, exhibited a reduction in M1 polarization over the first 72h after experimental TBI [225]. Of note, a progressive increase in the ratio of M1:M2 macrophages temporally correlated with evolving neurological injury, including white matter loss and reduced brain volume, after TBI [37, 187, 225, 226].…”
Section: Is Microglial Activation the Cellular Link Between Damp Rsupporting
confidence: 57%
See 2 more Smart Citations
“…TBI is defined as an alteration in brain function, or other evidence of brain pathology, caused by an external force (4), which results in immediate neuronal cell death, diffuse axonal injury, ischemia, and hemorrhage (5). These primary insults initiate a progressive cascade of secondary injuries, which include macrophage infiltration (6), neuro-inflammation (microglia and astrocyte activation associated with cytokine production), edema formation, oxidative stress, neuronal necrosis and apoptosis, and white matter atrophy (5). Secondary injuries can progress for years in patients and rodent models of TBI, and are the causes of the neurological and psychiatric deficits associated with the pathology (7).…”
Section: Introductionmentioning
confidence: 99%